Sanctions by the WTO Member Countries as a Catalyst for the Development of a Competitive Import Substitution by Domestic Enterprises - SAMARINA, Evgeneya Alikovna; PETROVA, Anastasia Dmitrievna; BLAZHENKOVA, Natalia Mihailovna; AZNABAEVA, Gulmariam Hisamytdinovna (Journal of Advanced Research in Law and Economics, 2017)
The article analyzes the economic and geopolitical situation prevailing in the world at the present stage of development. Imposition of sanctions by the European Union member states against the Russian Federation, which are in total disregard of the norms of the World Trade Organization, is nothing other than a sign of weakness in the face of a rapidly developing country aspiring to dominate and become the undisputed reference point for the entire international community. The authors conclude that a violation of the established norms by the World Trade Organization member countries did not result in the negative effects for the economy of our country expected by Western partners; on the contrary, it was an incentive to activate the latent reserves of domestic business entities to implement competitive import substitution.